The evasion in undergraduated in the Physics course: a look at the relation with knowledge (Research, Society and Development, 2020)
The ortagesh of qualified Physics teachers working in Basic Education remind us to the need to understand a phenomenon strongly present in the Physics courses by the country: university evasion. Thus, this study list the reasons presented by students in a situation of dropping out of the  undergraduate in the Physics course (between 2004 and 2014). In the light of the theory of knowledge and with regard to aspects of an affective nature, we noticed that the relationship with the other (particularly the teachers), in addition to difficulties in relation to the world (reconciling work and study) and elements of an epistemic dimension (high failure rates), were the reasons most cited aspects as cause of evasion for the analyzed group.